Soil quality response to land use change in a tropical semi-deciduous forest zone of Ghana - Alex Amerh Agbeshie; Richard Awuah; Vicentia Amoako; Roseline Awinmah Akurugu; Nana Bonsu Ofori-Adjei; Simon Abugre; Daniel Akoto Sarfo (Sustainable Environment)
Land use conversion is a significant driver impacting soil quality. Therefore, soil samples were collected in five different land use types, namely natural forest (NF), cocoa agroforestry (COA), agricultural land (AGL), reclaimed area (REM), and disturbed mined area (DIM), analysed for their biogeochemical attributes, and subjected to the principal component analysis (PCA) to identify the minimum data set (MDS) for soil quality index (SQI) computation. The highest soil water content, porosity, total nitrogen (TN), available potassium, magnesium and cation exchange capacity were recorded under the NF system. Higher inputs of litter addition, coupled with no soil disturbance, led to the highest MBC under the NF (626.40 Mg C kg−1). The PCA selected seven (7) soil indicators to form the MDS: TN, soil carbon (OC), organic matter (OM), nitrogen stocks (TNS), cadmium (Cd), silt, and pH. Subsequently, the SQI ranged from 0.45 to 0.78 and ranked as DIM < AGL < COA < NF < REM. The SQI revealed that the REM had higher quality, possibly due to the reintroduction of different fast-growing and N-fixing tree species. The finding highlights the essence of sustainable land management practices to enhance soil health and ecosystem stability. Thus, land managers could monitor the key soil indicators under the different land use systems to mitigate soil degradation and promote soil health and ecosystem sustainability. We recommend adopting sustainable land use practices such as agroforestry and restoration initiatives to restore disturbed areas and improve soil quality and ecosystem resilience.